ON THE NUMBER OF DIFFERENT ENTRIES IN INVOLUTORY MDS MATRICES OVER FINITE FIELDS OF CHARACTERISTIC TWO - Afifurrahman, Muhammad
Some criteria for a good MDS matrix in finite fields of characteristic two are being involutory and having few different elements. This final project investigates the number of different entries of an involutory MDS matrices of order 1, 2, 3, and 4 in finite fields of characteristic two.